Building mutual rewarding sponsor relationship between museums and corporations. - Casado-Molina, Ana María; Alarcón-Urbistondo, María del Pilar; van Riel, Cees B.M. (Taylor & Francis, 2023)
This paper proposes a theoretical model for the holistic description of the conditions to be met for a mutually beneﬁcial relationship between museums and sponsoring corporations, from the perspectives of both parties. Based on interviews of sponsorship managers in top Dutch museums and their sponsoring corporations, and the application of Grounded Theory, the categories and relationships that describe the model are identiﬁed. We conclude that for a successful sponsorship, both the commercial and cultural drivers behind this relationship must be considered, and the organisational performance, management and joint cooperation should be deemed satisfactory. Moreover, such sponsorships should be aligned with the demands and requirements of society.
Publicado en repositorio institucional: https://pure.eur.nl/en/publications/building-mutual-rewarding-sponsor-relationships-between-museums-a Autorización en correo RIUMA (07/01/25)
Keywords: Mecenazgo; Patrocinio; Museum sponsorship; Inter-organisational relationships; Successful sponsorship; Cultural sponsorship; Reputation risks; Alliances